TERAPI ISLAM ATAS KRISIS KEMANUSIAAN ERA MODERN - Nasri Hamang (KOMUNIDA : Media Komunikasi dan Dakwah, 2015)
This article exsplores humanities crisis in the modern era and it therapical methode in the Islam. The humanities crisis in the modern era, there is individualistic, consumerstic, materialistic, hedonistic, negatif competition, permissivistic and anxiety. The humanities crisis is very dangerous order Islam perspective. It will to spcae human being from the religion values, it can to bring human being be a secular. Therefore, is very urgen to know how Islam to tackle its. The methode which used in this explores is methode deductive. The exsplores result to prove that Islam to teach its therapical-approach shaped undestanding round human being is social creature, kind wealth.